2021
DOI: 10.5194/essd-13-1361-2021
|View full text |Cite
|
Sign up to set email alerts
|

Diets of the Barents Sea cod (<i>Gadus morhua</i>) from the 1930s to 2018

Abstract: Abstract. A new dataset on the diet of Atlantic cod in the Barents Sea from the 1930s to the present day has been compiled to produce one of the largest fish diet datasets available globally. Atlantic cod is one of the most ecologically and commercially important fish species in the North Atlantic. The stock in the Barents Sea is by far the largest, as a result of both successful management and favourable environmental conditions since the early 2000s. As a top predator, cod plays a key role in the Barents Sea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The NEA cod is a predator of the BS capelin as shown by diet studies [19,20] and we indeed found a negative effect of cod on capelin stock, similar to previous findings [35]. Conversely, capelin abundance is expected to have a positive effect on cod stock [36,37] and our results also support the claim.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The NEA cod is a predator of the BS capelin as shown by diet studies [19,20] and we indeed found a negative effect of cod on capelin stock, similar to previous findings [35]. Conversely, capelin abundance is expected to have a positive effect on cod stock [36,37] and our results also support the claim.…”
Section: Discussionsupporting
confidence: 92%
“…This high plasticity in its diet may explain our result that cod populations are not affected by capelin abundance when the latter is under a relatively high threshold of 209 billion individuals (note that the median capelin abundance during the studied period is 227 billion individuals, data ranging from 14 billion to 1016 billion individuals). In addition, a low capelin abundance has been associated with high herring Clupea harengus abundance, another major predator of capelin larvae in the BS [35,41] that is also part of the cod diet [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent works on historical stomach's contents of NEA cod in the Barents Sea indicate that before the collapse, the herring was much more abundant than capelin in the cod diet (Townhill et al, 2015(Townhill et al, , 2021. Such diet difference is another indication of the change of the link herring-capelin-cod after the collapses.…”
Section: Discussionmentioning
confidence: 97%
“…Since 1984, the NEA cod diet (fish sized 20–90 cm) is composed on average of only about 3% of herring and about 33% of capelin (Holt et al, 2019). Conversely, recent works on historical stomach's contents of NEA cod in the Barents Sea indicate that before the collapse, the herring was much more abundant than capelin in the cod diet (Townhill et al, 2015, 2021). Such diet difference is another indication of the change of the link herring‐capelin‐cod after the collapses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation